Evaluation of the Effectiveness of Oil and Gas Industrial Wastewater Treatment: A Case Study of PT Kilang Pertamina Internasional RU III Palembang: Evaluasi Efektivitas Pengolahan Air Limbah Industri Migas: Studi Kasus PT Kilang Pertamina Internasional RU III Palembang - Dewi Indriani; Prabowo Eka Soesanta; Subekti Nurmawati (​Institute for Researches and Community Services Universitas Muhammadiyah Palangkaraya, 2026)
Wastewater treatment in the oil and gas industry plays an important role in meeting environmental quality standards and preventing pollution. This study aims to evaluate the effectiveness of wastewater treatment at PT Kilang Pertamina Internasional RU III Palembang through a comparison of influent and effluent quality. The parameters analyzed include ammonia, Biochemical Oxygen Demand (BOD), Chemical Oxygen Demand (COD), sulfide, pH, and oil and fat. The study used a quantitative approach with paired comparative analysis based on 12 months of operational data. The normality test using Kolmogorov–Smirnov showed that some of the data showed a normal distribution so that hypothesis testing was continued using a paired t-test at a 95% confidence level (α = 0.05). The results showed an effective reduction of 58.97% (ammonia), 28.34% (BOD), 37.51% (COD), and 56.81% (oil and fat), while sulfide was relatively low (22.02%) and pH tended to be stable (-0.81%). The results of the paired t-test showed a significant difference (p < 0.05) between influent and effluent concentrations in the main parameters, indicating that the wastewater treatment system was working effectively. However, the suboptimal effectiveness of several parameters indicated the need for optimization of the treatment process.